The Application of the jurisprudential principle "No Harm and Reciprocating Harm" in the Saudi Criminal Procedure Law - Almazyed, Shahad Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2025)
The importance of the research lies in linking the provisions of legal systems to jurisprudential principles as a foundation for the system, highlighting its reliance on Islamic Sharia rules, and enriching the legal texts with jurisprudential material that benefits everyone working in the judicial field, including judges, lawyers, and others. Many provisions of the criminal procedure system include rulings and measures related to the principle of "no harm and no reciprocating harm."The research aims to clarify the impact of applying the principle of "no harm and no reciprocating harm" in the criminal procedure system, explain the application of rules derived from this principle in the criminal procedure system in cases of independent harm, and illustrate the application of these rules in cases of conflicting harm. It also aims to show the role of this principle in the provisions of the Saudi criminal procedure system in ensuring procedural fairness by limiting the abuse of power and strengthening the right of victims to compensation, thus achieving a balance between public interest and individual rights. The researcher followed an inductive and analytical approach, starting from the major legal principle of "no harm and no reciprocating harm," and deduced its impact on the provisions of the criminal procedure system, analyzing these provisions to assess their alignment with this principle.One of the key findings of the researcher is that the major jurisprudential principle of "no harm and no reciprocating harm" has an impact on many provisions of the criminal procedure system. One of the most prominent recommendations made by the researcher is to focus on studying jurisprudential principles and their effects on the provisions of legal systems, as they demonstrate the comprehensiveness of Islamic Sharia and its capacity to address all issues and emerging cases.
Keywords: Criminal procedures; Islamic legal maxims; Criminal law